Addition of Transversus Abdominis Plane Block to Conventional Pain Regimens in Robotic Sacrocolpopexy Procedures—A Pilot Randomized Controlled Trial (SACROTAP). Issue 2 (February 2023) - Zoorob, Dani; Tsolakian, Ibrahim; Shuffle, Eric; Perring, Paul; Maxwell, Rose
Abstract : Importance: There have been no randomized trials assessing the benefits of integration of transversus abdominis plane (TAP) blocks in sacrocolpopexy procedure postoperative pain management. Objective: The aim of this study was to assess the variation in pain perception upon adding TAP blocks to conventional oral pain medications in patients undergoing sacrocolpopexy. The primary outcome was the reduction in pain reported using the numeric rating scale (NRS) among patient groups. The secondary outcome was the change in narcotic analgesic use postoperatively. Study Design: This was a prospective double-blind, pilot randomized controlled trial of women undergoing robotic sacrocolpopexy, with and without supracervical hysterectomy, with 20 patients enrolled in each arm. Randomization included receiving a TAP block in addition to the conventional analgesic regimen. Results: A total of 48 women were approached to participate in the study; 40 women provided consent (20 per study arm) and completed the 7-day follow-up. Patients receiving a TAP block had lower NRS pain scores at 4 hours postoperatively (4.95 ± 0.76 vs 5.50 ± 0.61, P = 0.02), 7 days postoperatively (2.20 ± 1.11 vs 3.15 ± 1.04, P = 0.008), and lower cumulative NRS pain scores at 48 hours postoperatively (14.90 ± 2.2 vs 16.60 ± 2.04, P = 0.02) and 7 days postoperatively (17.10 ± 2.63 vs 19.75 ± 2.65, P = 0.003) than patients not receiving a block. Patients in the intervention group also had lower cumulative morphine milliequivalents at 7 days postoperatively (17.25 ± 10.7 vs 29.25 ± 14.53, P = 0.005). Conclusion: Use of TAP blocks in robotic sacrocolpopexy cases, with or without concurrent hysterectomy, may reduce postoperative pain and narcotic medication needs.